Fatores ambientais na produção de ovos com casca vítrea, qualidade de ovos e espectroscopia de casca - Carvalho, Letícia Souza Silva (2018)
The vitreous eggshell is often on farms at retail points, however, the literature on the subject in question is scarce. Therefore, the objective of this study was to evaluate the influence of temperature and air humidity and the age of laying hens on the production of eggs of vitreous shell, egg quality and shell spectroscopy. For the study, 200 laying hens of the 60 week old, Dekalb White strain were used. For four months, the eggs produced were daily classified into eggs normal and vitreous eggshell. Four dataloggers recorded temperature and air humidity data that were later parameterized to egg production data. Was realized analysis of variance of temperature, humidity and percentage of vitreous eggshell and the means were compared by the Tukey test. The ITU (Temperature and Humidity Index) was calculated to assess the thermal comfort of the birds and categorized into comfort, mild discomfort, moderate, severe and life-threatening. The correlation between ITU and the percentage of eggs vitreous eggshell and the multivariate correlation between temperature associated with air humidity and incidence of vitreous eggshell were tested. The ITU, temperature and humidity air, showed a moderate and substantial correlation on the incidence of eggs with vitreous eggshell. There was a substantial correlation between the association of temperature and air humidity with the incidence of vitreous eggs. To evaluate the quality and bromotological composition of the eggs, three samples of 20 eggs were made for each type of egsshell, divided into five replicates containing four eggs. In the first and last collection, another 20 eggs of each type of eggshell were selected for eggshell resistance test. Haugh units, yolk, yolk and albumen pH, percentages of yolk, albumen and eggshell, percentages of dry matter, mineral matter, crude protein and ethereal extract of yolk were evaluated for internal quality. For shell quality, the average porosity per cm2, shell thickness and percentages of mineral matter, calcium and phosphorus were measured. The results were submitted to analysis of variance and the means were compared by the Tukey test. Although the quality and bromatological composition of the did not differ the eggshells with vitreous appearance had a higher thickness and a smaller number of pores. To characterize the eggshell spectra, six eggs of normal shell and six eggs of vitreous shell had their internal contents removed. Three points in the equatorial region of the shell were analyzed by Raman Spectroscopy. Then, two fragments of the equatorial region of each eggshell were obtained to obtain the spectra by ATR-FTIR. Greater organic content was observed in the vitreous eggshell. It is concluded that the ITU and the association of temperature and humidity air can influence the incidence of eggs of vitreous eggshell, however, the vitreous aspect of the shell does not have negative effect on the quality and bromatological composition of the eggs, however it was observed the presence of greater organic content in the vitreous eggshell, as well as differences in the distribution of the compounds among the shell types.